Evaluating & comparing microplastic uptake by different groups of freshwater invertebrates - Tuncer, Gülşen Nilay (Graduate School, 2023)
Microplastics (<5 mm in diameter or length), which has become an emerging concern in recent years, are ubiquitous in aquatic ecosystems. Although there are abundant studies on the marine ecosystem in the literature, the increasing number of studies on freshwater are still very limited. In addition to reporting the presence of microplastics in freshwater, their interaction with aquatic organisms has also been the subject of research with increasing interest in recent years. Mechanisms related to encounter, interaction, uptake and effects of microplastics with organisms are still under investigation. However, information obtained from both field and laboratory studies is not yet fully understood due to uncertainties and lack of information on the risks of microplastics on humans and animals. For this, it is of great importance to compile and compare research studies. Freshwater invertebrates have also been the subject of microplastic research. Since the ingestion by freshwater invertebrates is the most common mechanism of uptake of microplastics, laboratory studies are conducted about the number of ingested particles and also factors affecting ingestion. Additionally, the effects of microplastics on vital functions such as mortality, reproduction and feeding behaviour of organisms after ingestion are still being investigated. Given the information in the literature, the general focus of this thesis is to examine the factors having influence on the ingestion of microplastics and to determine which freshwater invertebrates are more susceptible by comparing them with quantitative data. Laboratory studies on freshwater invertebrates have thorougly researched and quantitative data adapted for comparison between studies. In particular, the uptake rate was calculated to compare the uptake of microplastic by invertebrates. Uptake rate was evaluated and compared in terms of factors such as concentration and exposure time affecting microplastic uptake. In this context, more specifically, the objectives of the study are: 1) Describing the feeding strategies of various groups of freshwater invertebrates; 2) Evaluating their uptake mechanisms of microplastics; 3) Comparing microplastic ingestion by organisms with different feeding strategies and evaluating the microplastic ingestion; 4) Determination of uptake rate and egestion rate of microplastic by Daphnia magna with the AQUASIM analysis tool. The integration of the data presented by Rist et al. [13] into the AQUASIM tool enabled the determination of the 'quptake' microplastic uptake rate and 'Krel' microplastic egestion rate, which provides valuable insights into the weight-based microplastic uptake at specific time intervals. This finding contributes to the existing literature by enhancing our understanding of microplastic uptake dynamics. The analysis revealed a ' quptake' microplastic uptake rate of 20±2.21 1/day for 2 µm microplastics and 1±0.08 1/day for 100 nm microplastics in D. magna. The egestion rate, ' Krel', was found to be 0.19±0.08 1/day for 2 µm and 0.22±0.09 1/day for 100 nm microplastics. The modeling results indicate that larger particles are ingested more frequently but removed at a slower rate. Therefore, it can be inferred that the potential damage caused by 2 µm microplastics, which are also suitable in size for Daphnia magna's food, could be more significant. Laboratory and field studies were collected and seperately tabulated to compare the quantitative microplastic ingestion results between freshwater invertebrate groups with different feeding strategies. The collected numerical data were hardly amenable to comparison due to large variations in the studies such as concentration, food availability, exposure period, size and shape of MPs. All those factors effecting the ingestion of microplastic were compared in detail by using the uptake rate calculations. The effects of those variables on microplastic ingestion have been discussed more in detail in Section 3. This study also emphasized the necessity of more standardized laboratory experiments. In addition, in order to compare the studies more accurately and consistently, some data in reporting should be specified with the help of a guideline.
Farklı tatlı su omurgasız gruplarının mikroplastik alımının değerlendirilmesi ve karşılaştırılması
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2023
Keywords: Microplastics; Aquatic ecosystems; Marine ecosystem